Association between hypnotic medication use and in-hospital falls among older adults: A multicenter landmark analysis - Takuya Nishino; Yoshiaki Kubota; Yasuo Miyagi; Nari Tanabe; Fumiko Yamaguchi; Hiroki Ito; Shizuka Soh; Ayako Yano; Masako Mizuno; Chol Kim; Yosuke Ishii; Yukihiro Kondo; et al. (PLoS ONE, 2026)
Background Hypnotics are frequently prescribed to hospitalized older adults, but comparative evidence on fall risk across hypnotic classes remains inconsistent, partly due to confounding by indication and inadequate consideration of time at risk during hospitalization. Methods We conducted a retrospective multicenter landmark analysis using administrative claims and electronic medical records from two acute-care hospitals in Japan (2018–2024). A day-7 landmark was defined, including patients aged ≥65 years who remained hospitalized and fall-free through hospital day 7. Sustained hypnotic exposure during hospital days 4–7 (≥2 days) was categorized as no sustained use, benzodiazepines/Z-drugs (BZ/Zs) alone, orexin receptor antagonists or ramelteon (ORA/Ram) alone, or combination therapy. The primary outcome was time to first in-hospital fall during hospital days 8–37. Cox proportional hazards models with multiple imputation were used. Competing-risk analyses and propensity score–matched comparisons between single-class users were conducted as sensitivity analyses. Results Among 61,663 patients, 3,884 (6.3%) experienced an in-hospital fall after the landmark. Compared with no sustained hypnotic use, adjusted hazard ratios (HRs) for falls were 1.42 (95% CI, 1.24–1.64) for BZ/Zs, 1.46 (95% CI, 1.25–1.70) for ORA/Ram, and 1.42 (95% CI, 1.05–1.91) for combination therapy. Results were consistent in competing-risk analyses. In propensity score–matched analyses restricted to single-class users, fall risk did not differ significantly between BZ/Zs and ORA/Ram (adjusted HR, 0.98; 95% CI, 0.75–1.28). Conclusions Sustained hypnotic use during hospitalization was associated with a higher incidence of in-hospital falls among older adults. After adjustment for measured clinical factors and treatment selection, no significant difference in fall risk was observed between BZ/Zs and ORA/Ram.